Age- and Maturity-Related Variations in Morphology, Body Composition, and Motor Fitness among Young Female Tennis Players - Söğüt, Mustafa (2019)
The purpose of this study was to examine the effects of age and maturity on anthropometric and various fitness characteristics in young competitive female tennis players. Sixty-one players, aged 10.4-13.2 years (11.8 ± 0.8) were measured for standing and sitting heights, body mass, skinfolds, grip strength, and agility, and dichotomized into two age (U12 and U14) and maturity (earliest and latest) groups according to their chronological age and maturity status. The results revealed significant age effects for stature, sitting height, leg length, and hand grip in favor of the older players. Girls contrasting in maturation differed significantly for all anthropometric and physical performance variables except for body mass index (BMI), body fat percentage (BF%), and hexagon agility test. The earliest maturing group showed significantly higher values for anthropometric measures and better results in the hand grip test than the latest maturing group. After controlling for chronological age, differences were revealed between contrasting maturity groups in stature, sitting height, BF%, and the hand grip test. The findings highlight the age- and maturity-related trends in body size and muscular strength among young female tennis players in the pubertal period. Nevertheless, the differences in the body composition and agility of the contrasting age and maturity groups were negligible.